Clinical pharmacy and therapeutics - Walker, Roger;Whittlesea, Cate (Edinburg, New York : Churchill Livingstone, 2012)
Now in its fifth edition, this best-selling, multidisciplinary textbook continues to draw on the skills of pharmacists and clinicians to present optimal drug regimens. The authors integrate an understanding of the disease processes with an appreciation of pathophysiological processes, clinical pharmacy and the evidence base.
Section 1. General -- section 2. Life stages -- section 3. Therapeutics -- Section 4. Appendices.
Includes bibliographical references and index.
Keywords: CHEMOTHERAPY